Goodhart's Law and the Gaming of UK Public Spending Numbers. Issue 2 (4th March 2021) - Hood, Christopher; Piotrowska, Barbara
Abstract: Goodhart's Law, originally inspired by money-supply indicators, predicts high-consequence administrative numbers tend to be gamed out of meaningfulness. This paper argues that, in addition to the well-documented manipulation of aggregate input numbers at the top-levels of decision making and performance indicators used for output control at the lower level, meso-level gaming happens also on the input side of public expenditure planning and control. A key mechanism through which it operates is creative categorization in the classification of units of spending. Based on a UK study, we explore three questions: can we find evidence for the existence of gaming in public expenditure control, how does the creative categorization work and how material or consequential is it? Using case studies of "protected" spending, public-private partnerships and accounting changes, we show that gaming understood as creative categorization is readily observable in UK public expenditure control and Goodhart's Law effects can indeed be material or consequential, both in scale and in their implications for government accountability. We conclude that creating new spending categories to control public expenditure and limit gaming is a two-edged sword since it itself creates new opportunities for gaming.